Conjugated Oligothiophene Derivatives Based on Bithiophene with Unsaturated Bonds as Building Blocks for Solution‐Processed Bulk Heterojunction Organic Solar Cells. Issue 24 (25th November 2016) - Cui, Chaohua; Wu, Yue; Cheung, Man‐Sing; Ho, Cheuk‐Lam; Dong, Qingchen; Lin, Zhenyang; Li, Yongfang; Wong, Wai‐Yeung
Abstract: A new building block ATVTA that uses stiff carbon–carbon triple bonds (A) on 1, 2‐di(2‐thienyl)‐ethene (TVT) has been developed. Oligothiophene derivativesS‐01 with a TVT unit, S‐02 with a 5, 5′‐diethynyl‐2, 2′‐dithienyl (AT2) unit andS‐03 with ATVTA were synthesized to compare their effects in a systematic study. Due to the better π‐conjugation extension of the TVT unit, S‐01 exhibits the most red‐shifted absorption profile among them, whereasS‐02 possesses the deepest HOMO level. While the HOMO level ofS‐03 is down‐shifted by 0.02 eV relative to that ofS‐01, the alkyne linkages can effectively down‐shift the HOMO level. By replacing the terminal units ofS‐03 with stronger electron acceptors, S‐04 andS‐05 exhibited broader absorption profiles and lower HOMO levels than those ofS‐03 . Organic solar cells based on these molecules were fabricated and anS‐03 :PC60 BM (1:1, w/w) based device afforded the highest V oc value of 0.96 V and a power conversion efficiency (PCE) of 2.19 %. Abstract : Conjugation rules ! A new building block ATVTA that uses stiff carbon–carbon triple bonds (A) as the linkages on a 1, 2‐di(2‐thienyl)‐ethene (TVT) unit has been developed. The effects of three building blocks (TVT, AT2 and ATVTA units) and the nature of the terminal electron acceptors in several conjugated oligothiophene derivatives were studied systematically.